The Evaluation of Fasting Plasma Glucose (FPG) Levels in Hypertensive Patients Using Calcium Channel Blocker (CCB) Drugs Class in Undata Regional Hospital: Evaluasi Kadar Glukosa Plasma Puasa (GPP) pada Pasien Hipertensi Menggunakan Obat Kelas Pemblok Kanal Kalsium di Rumah Sakit Daerah Undata - Rumi, Amelia; Fitriana, Anggun (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: Hypertension plays a major role in the development of heart disease which is one of the most leading causes of death worldwide. Antihypertensives must be selected carefully to avoid affecting metabolic parameters. A risky case involving the increase of plasma glucose levels using Calcium Channel Blocker (CCB) antihypertensive, amlodipine, has been reported. Objectives: This study aims to examine the effects of CCB treatments on blood glucose levels in hypertensive patients at the Undata District General Hospital of Central Sulawesi Province. Material and Methods: This study used a cross-sectional design with a prospective approach. The instruments & materials used in this study are Accu-Chek Performa glucometer along with the patient's blood sample material. The research subjects were 31 patients who met the inclusion criteria; patients had been treated with CCB therapy for 3 months, patients were not diagnosed with diabetes mellitus, andpatients did not use drugs that might affect the blood glucose levels. Results: The results showed an average value of fasting plasma glucose (FPG) levels of hypertension patients using CCB class showed an increase from baseline of 124,619 mg/dL to 141,612 mg/dL with a difference of 16,993 mg/dL. Statistical analysis conducted also obtained a significance value of p 0,000 which indicates that the use of amlodipine can significantly increase fasting patients' plasma glucose levels. Conclusions: If observed clinically, the increasing in fasting plasma glucose values ​​falls into the category of mild to moderate hyperglycemic.